2006
DOI: 10.1007/s10661-005-9168-3
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of PM2.5 and PM10-2.5 in PM10 Fraction in Ambient Air Due to Vehicular Pollution in Kolkata Megacity

Abstract: This research paper aims at establishing baseline PM(10) and PM(2.5) concentration levels, which could be effectively used to develop and upgrade the standards in air pollution in developing countries. The relative contribution of fine fractions (PM(2.5)) and coarser fractions (PM(10-2.5)) to PM(10) fractions were investigates in a megacity which is overcrowded and congested due to lack of road network and deteriorated air quality because of vehicular pollution. The present study was carried out during the win… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(18 citation statements)
references
References 21 publications
2
14
0
1
Order By: Relevance
“…The high concentrations of fine particulates at all of these sites can be attributed to the fact that these cities are highly populated metropolitan cities with a very high associated fine mode aerosol contribution from fossil fuel burning including vehicular exhaust. The average PM 2.5 mass concentration over Kolkata was found to be similar to that reported by Das et al [32] (179 lg m -3 ) for the winter season. Moreover, elevated PM 2.5 concentrations at these sites could be attributed to the fact that the air masses received at these sites were observed to originate and undergo transport in the IGP itself and could thus be carrying fine mode continental pollutants to these sites.…”
Section: Resultssupporting
confidence: 88%
“…The high concentrations of fine particulates at all of these sites can be attributed to the fact that these cities are highly populated metropolitan cities with a very high associated fine mode aerosol contribution from fossil fuel burning including vehicular exhaust. The average PM 2.5 mass concentration over Kolkata was found to be similar to that reported by Das et al [32] (179 lg m -3 ) for the winter season. Moreover, elevated PM 2.5 concentrations at these sites could be attributed to the fact that the air masses received at these sites were observed to originate and undergo transport in the IGP itself and could thus be carrying fine mode continental pollutants to these sites.…”
Section: Resultssupporting
confidence: 88%
“…The very low PM 2.5 /PM 10 ratios also show that coarse (resuspended) particles are important. Unpaved roads as a source for high concentrations in residential areas have also suggested by Etyemezian et al (2005) and Das et al (2006) but lower values were found by Sharma and Maloo (2005) and Kaushik et al (2006) due low traffic volumes.…”
Section: Diurnal Peaksmentioning
confidence: 96%
“…Furthermore the descriptions of the sites can be rather vague. However, residential areas can have higher concentrations than commercial (Jayaratne and Verma 2001;Etyemezian et al 2005;Das et al 2006) due to domestic emissions or unpaved roads but also lower (Sharma and Maloo 2005;Kaushik et al 2006) because of less traffic. The influence of nearby traffic has been studied by Jackson (2005), Gupta et al (2006) and Kumar and Joseph (2006).…”
Section: Introductionmentioning
confidence: 99%
“…In view of the air quality status, some of the Indian cities are considered to be among the most polluted cities in the world (Mitra and Sharma, 2002). It is well known that PM 10 is a better indicator of total suspended particulate matter (Das et al, 2006). These findings therefore, highlight the need for monitoring of PM 10 particles for the quantification of particulate load in the ambient air and also to suggest control measures for these particles in the air.…”
Section: Particulate Matter -Significancementioning
confidence: 96%
“…Epidemiological evidence has even attributed PM 10 in cancer and in some cases even premature death. The relative strength of association of air pollutants with mortality were reported as follows: PM 2.5 ≥ PM 10 ≥ SO 2 ≥ H + ≥ O 3 ≥ NO x (Dockery et al, 1992;Das et al, 2006). Further it has been found that for each 10 μg/m 3 increase in PM 10 Concentration, there is an estimated increase in mortality by almost 1 per cent (Dockery and Pope, 1994;Ostro, 1996;Das et al, 2006).…”
Section: Particulate Matter -Significancementioning
confidence: 98%